Enterprise Resource Planning: A Managerial & Technical Perspective - Parthasarathy, S (New Age International Ltd, 2007)
Management is becoming a more and more exacting job today. Competition is the spirit of the enterprise now. Accuracy and speed are the most important requirements in this. And it now involves the integration and comprehension of details and information from many segments of the business. The daunting task is, however, made possible by the revolutions in Information Technology. Enterprise Resource Planning (ERP) is primarily an enterprise wide system that can accommodate corporate mission, objectives, attitudes, beliefs, values, operating style and people who make the organization. The inadequacy of the old system is the mother of this invention. Enterprise Resource Planning (ERP): A Managerial and Technical Perspective is designed as a textbook that bridges the unaddressed gap between managerial issues and technical issues, providing also some case studies.